Discovery of the sponge-associated caridean genus Paralebbeus in New Zealand and southeastern Australia: P. pegasus sp. nov. (Crustacea: Decapoda: Thoridae) - Ahyong, Shane T. (Zootaxa, 2019)
Deepwater sampling in New Zealand and southern Australian waters over the past two decades has significantly improved knowledge of all invertebrate groups, including decapod crustaceans. Thorid shrimps of the genus, Paralebbeus Bruce & Chace, 1986 are associated with deepwater hexactinellid sponges, with four species known to date from scattered localities in the southwestern Indian Ocean, northwestern Australia, Southeast Asia and the northwestern Pacific including Japan. Paralebbeus pegasus sp. nov. is described from New Zealand and southeastern Australia, representing the first record of the genus from the temperate southwestern Pacific. The new species of Paralebbeus is unique in the genus for having meral spines on pereopods 3–5. A key to the species of Paralebbeus and global distribution map are provided.